PENGARUH FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan Farmasi Yang Terdaftar Di BEI Tahun 2005-2014) - Muhammad Raymon Hidayat; Sri Hermuningsih (Universitas Sarjanawiyata Tamansiswa, 2018)
This research performed in order to test influence of fundamental factor (EPS, NPM, ROA, and DER) toward stock return of farmacy companies that listed in Indonesia Stock Exchange for period 2005-2014.The result of this research show DER have significant effect towards stock return.. And EPS, NPM, ROA don’t have significance effect toward stock return. While, four independent variabel EPS, ROA, DER, and NPM to have influence toward return on equity at level of significance 5% as 0,000%. Predictable of the three variables toward return on equity is 18,6%. While the rest 81,4% is affected by other factors is not included into the study model.Kata Kunci :Earning per Share, Net Profit Margin, Return on Asset, Debt to Equity Ratio and Stock Return